Preschool zombies: embodied, socio-(re)enacted, productive spatial literacies. Issue 6 (2nd November 2022) - Powell, Sarah J.; Somerville, Margaret
ABSTRACT: In performing the zombie game, children enact embodied literacies through movement, gesture, and sound, and through incorporating the materiality and the spatiality of the outdoor area. They communicate in many ways, both brutal and subtle, enacting their understandings with each other as well as with other adults. The repeated performance seems to function as a refrain that provides security and calm in a highly unstable world. It de- and re-territorializes the space of the preschool, making and re-making children's worlds. The performance of the game is an embodiment of social context, the enactment of the absorbed lived experience that constitutes a becoming for both zombie child and additional needs child. Through this repeated game we come to understand the agency of these children differently in their capacity to re-create their worlds through play.